W co i czym się bawić? Wskazówki w zakresie organizacji zabaw, wykonywania i wykorzystywania zabawek dziecięcych na ziemiach polskich w drugiej połowie XIX i na początku XX wieku – wybrane problemy - Monika Nawrot-Borowska (Problemy Wczesnej Edukacji)
This article focuses on instructions and advice on making toys for children and by children, recommendations regarding their use, as well as organization of children’s games. The temporal scope covers the second half of the nineteenth and early twentieth centuries. The aim of the present study is to describe selected ideas for making children’s toys published in pedagogical press, women’s magazines, and press for children and adolescents, as well as methodological pedagogy guidebooks. The article also describes recommendations for the use of the so-called educational toys, used for learning through play. The text contains critical descriptions of selected guides containing suggestions on the organization of children’s games, addressed to children, parents and educators, as well as inspirations for games found in the literature and press addressed to the youngest readers.